El aprendizaje significativo como estrategia de enseñanza de área y perímetro en noveno grado de un colegio público de Bogotá (2024)
This undergraduate thesis is framed within the modality of a scientific article submitted to the Praxis journal at the University of Magdalena. The article proposes that 9th-grade students in Colombia are not adequately developing mathematical competencies, as reflected in the 2022 Saber test results. Furthermore, differences are observed between students in public and private schools. To address this issue, a didactic strategy based on meaningful learning is proposed to strengthen the concepts of area and perimeter among 9th-grade students at Gustavo Restrepo School.